Proteomic measures of gamma oscillations. Issue 8 (August 2019) - Byrum, Stephanie D.; Washam, Charity L.; Tackett, Alan J.; Garcia-Rill, Edgar; Bisagno, Veronica; Urbano, Francisco J.
Abstract: Background: Gamma oscillations serve complex processes, and the first stage of their generation is the reticular activating system (RAS), which mediates the gamma-activity states of waking and paradoxical sleep. We studied whether the pedunculopontine nucleus (PPN), part of the RAS in which every cell manifests intrinsic gamma oscillations, undergoes changes resulting in distinctive protein expression. New method: We previously found that a histone deacetylation inhibitor, trichostatin A (TSA), acutely (30 min) blocked these oscillations. We developed a proteomic method for sampling stimulated and unstimulated PPN and determining protein expression in 1 mm punches of tissue from brain slices subjected to various treatments. Results: We compared brain slices exposed for 30 min to TSA (unstimulated), to the cholinergic agonist carbachol (CAR), known to induce PPN gamma oscillations, or exposed to both TSA + CAR. Comparison with existing methods: Label-free proteomics provides an unbiased and sensitive method to detect protein changes in the PPN. Our approach is superior to antibody-based methods that can lack specificity and can only be done for known targets. Proteomics methods like these have been leveraged to study molecular pathways in numerous systems and disease states. Conclusions: Significant protein changes were seen in two functions essential to the physiology of the PPN: cytoskeletal and intracellular [Ca 2+ ] regulation proteins. TSA decreased, while CAR increased, and TSA + CAR had intermediate effects, on expression of these proteins. These results support the feasibility of the methods developed for determining proteomic changes in small samples of tissue participating in the most complex of brain processes.